Thermo-economic analysis, optimisation and systematic integration of supercritical carbon dioxide cycle with sensible heat thermal energy storage for CSP application - Thanganadar, Dhinesh; Fornarelli, Francesco; Camporeale, Sergio; Asfand, Faisal; Gillard, Jonathon; Patchigolla, Kumar (Elsevier, 2021)
Integration of thermal energy storage with concentrated solar power (CSP) plant aids in smoothing of the variable energy generation from renewable sources. Supercritical carbon dioxide (sCO2) cycles can reduce the levelised cost of electricity of a CSP plant through its higher efficiency and compact footprint compared to steam-Rankine cycles. This study systematically integrates nine sCO2 cycles including two novel configurations for CSP applications with a two-tank sensible heat storage system using a multi-objective optimisation. The performance of the sCO2 cycles is benchmarked against the thermal performance requirement of an ideal power cycle to reduce the plant overnight capital cost. The impacts of the compressor inlet temperature (CIT) and maximum turbine inlet temperature (TIT) on the cycle selection criteria are discussed. The influence of the cost function uncertainty on the selection of the optimal cycle is analysed using Monte-Carlo simulation. One of the novel cycle configurations (C8) proposed can reduce the overnight capital cost by 10.8% in comparison to a recompression Brayton cycle (C3) for a CIT of 55°C and TIT of 700°C. This work describes design guidelines facilitating the development/ selection of an optimal cycle for a CSP application integrated with two-tank thermal storage.
Keywords: Central Power Tower; Multi-objective optimisation; Thermal Energy Storage; Overnight Capital Cost; CSP; Supercritical CO2 cycle